Applied computing and information technology - Lee, Roger (Studies in computational intelligence ;, 2017)
This edited book presents scientific results of the 4th International Conference on Applied Computing and Information Technology (ACIT 2016) which was held on December 12-14, 2016 in Las Vegas, USA. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. The aim of this conference was also to bring out the research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them. The conference organizers selected the best papers from those papers accepted for presentation at the conference. The papers were chosen based on review scores submitted by members of the Program Committee, and underwent further rigorous rounds of review. This book captures 11 of the conference's most promising papers, and the readers impatiently await the important contributions that they know these authors are going to bring to the field of computer and information science.